Gasification of microalgae Chlorella vulgaris for synthesis gas production - ., Abdul Raheem (2015)
Microalgae have been used as a substrate for biofuel production due to numerous advantages, including fast growth rate, ability to grow with/without land and accumulate substantial amounts of carbohydrates, lipids and proteins. However, current production of alternative fuel from microalgal biomass (biodiesel and bioethanol) involves lengthy processing steps. Thermochemical conversion is proven technology for higher conversion efficiency of biomass into biofuel and shorter production period compared to other conventional methods such as biochemical. However, low production yield of synthesis gas (syngas) produced from the process hinder their conversion into a higher value of fuel products. This can be realized by optimizing its process conditions for high production yield of the syngas. In this study, microalgal biomass, Chlorella vulgaris, is thermochemically gasified for syngas production. The study involves three stages include characterization of the C.vulgaris biomass, identification of the process parameters (reactor temperature, C.vulgaris biomass loading, and heating rate) and optimization for high syngas production. The characterization of C. vulgaris biomass explains that the thermal degradation behavior of the biomass can be divided into three major stages; (1) moisture removal, (2) devolatization of carbohydrates, protein and lipids and (3) degradation of carbonaceous material. A degradation rate of 80% was obtained at the second phase of the combustion process in the presence of air whilst a degradation rate of 60% was obtained under N2 atmosphere at the same phase. The biomass was further gasified for syngas production using a Temperature Programed Gasifier (TPG). The effect of three different process parameters, temperature (700, 800, and 900℃), C. vulgaris biomass loading (0.1, 0.25, and 0.5 g), and heating rate (5, 10, and 20℃ min-1) were investigated. The maximum H2 production was found at 800°C (45.9 ± 0.5 mol %, 0.35 mmol g-1) with a biomass loading of 0.5 g (39.9 ± 1.5 mol %, 0.62 mmol g-1). No significant effect of heating rate was observed on H2 production. The activation energy values in air atmosphere, based on the Kissinger method, were evaluated to be 45.38 ± 1.0 kJ mol-1 (1st stage), 61.20 ± 0.5 kJ mol-1 (2nd stage) and 97.22 ± 0.5 kJ mol-1 (3rd stage). Furthermore, the optimization of microalgal gasification for syngas production was conducted using a high temperature horizontal tubular furnace. Four response variables (H2, CO, CO2, and CH4) were optimized under varying conditions of temperature (500-900 ℃), C. vulgaris biomass loading (0.6 - 2.5 g), heating rate (5 - 25℃ min-1), and equivalent ratio (ER = 0.1 - 0.35). The optimization study was carried out using Central Composite Design (CCD). Temperature was found as the most significant process parameter influencing H2 production followed by C. vulgaris biomass loading and heating rate. A maximum H2 yield of 41.75 (0.66 mmol g-1) mol % was obtained at a temperature of 703℃, C. vulgaris loading of 1.45 g, heating rate of 22℃ min-1, and ER concentration of 0.29. Statistical analysis showed that the generated models were sufficiently in agreement with the experimental results. It was concluded that direct gasification of C. vulgaris biomass in the presence of air has a significant potential for commercial-scale production of syngas products under optimum economy. Hence the findings from this study are expected to resolve the problems that are being encountered with current conversion methods through the provision of numerous environmental and cost benefits.